(untitled) (Research, Society and Development, 2025)
The objective of this study was to perform a meta-analysis to compare ESRD outcomes, measured by GFR, in children with PUV treated with two distinct therapeutic strategies: CT followed by delayed resection (DR) and REI. This meta-analysis compared cystostomy with delayed resection (CTRT) and isolated endoscopic resection (REI) in preventing end-stage renal disease (ESRD) in children with posterior urethral valves (PUV). Twelve studies (2011–2023) involving 770 patients were analyzed after screening 1,904 records. Results showed 29.28% of CTRT patients progressed to ESRD versus 18.15% in the REI group, but without statistical significance (absolute difference: -11.13%; 95% CI: -33.50% to 11.25%; *p* = 0.306). Both approaches demonstrated similar efficacy, with the choice depending on obstruction severity, healthcare resources, and surgeon expertise. CTRT may be preferable in resource-limited settings, while REI is feasible in specialized centers. Study limitations included heterogeneity and lack of data on PUV severity. The findings support individualized treatment and highlight the need for long-term follow-up studies.